Public Opinion On The Formation Of The Asean Economic Community: An Exploratory Study In Three Asean Countries - Benny, Guido; Tham, Siew; Ramli, Rashila (Penerbit Universiti Sains Malaysia (USM Press), 2015)
In 1997, 10 Association of Southeast Asian Nations (ASEAN) member states envisaged an ASEAN Economic Community (AEC) with free flows of goods, services and investments, and freer flows of capital features. In contrast to the process of establishing economic integration in the European Union, the process in ASEAN has never directly engaged the public. This study aims to gauge public opinion on the AEC through a survey research conducted in 11 major cities in Indonesia, Malaysia and Singapore. It investigates the extent of public attitudes and aspirations in four dimensions—support, commitment, perceived benefits and aspiration—among the public in the three countries. Survey results show that the attitudes of the public were positive, but there were differences in the extent of support, commitment and perceived benefits. The study also finds that they seem to aspire for a different kind of integration from the European format of regional integration. In addition, comparison statistics showed that the Malaysian and Indonesian public exhibited more positive attitude and higher aspiration for economic integration. The finding implies that the ASEAN Secretariat—together with national governments—needs to formulate effective strategies to maintain positive attitudes and support for the integration initiatives. It further suggests that ASEAN should continuously monitor public opinion on the region's economic integration and develop strategies for fostering and maintaining good support from the public for further deepening the economic integration process.